USING PICTURE CARDS IN IMPROVING STUDENTS’ READING ABILITY FOR ELEMENTARY STUDENTS - Hasan Hasan; Taufik Taufik; Kasman Kasman; Angga Putra; Eka Yulianti (Sean Institute, 2023)
Indonesian language subjects cover all aspects of language, namely listening, speaking, reading and writing. The ability to read is always in every learning theme. This proves that reading is a very important skill. This study aims to improve beginning reading skills through the media of picture word cards at SDN 40 Woja. This is motivated by the low ability of children in early reading. This research model used a classroom action research (CAR) through two cycles namely cycle 1 and cycle 2 that consisted of planning, implementation, observation and reflection. The results of the study show that the beginning reading comprehension of grade I students can be improved by using picture word cards as media. This is evidenced by the results of the initial reading improvement. In the pre-action state that it achieved a score of Cycle II of 95.57%, its average strength was 42.59%, increased by 25.75%, reached 68.34% in Cycle I, and experienced an increase of 27.23% from Cycle I to Cycle II. It can be concluded that that word card media can improve beginning reading skills from Cycle I to Cycle II at SDN 40 Woja